Maxillary Ameloblastoma with Local Recurrence, Orbital Invasion, and Systemic Metastases: A Case Report and Review of the Literature - Taylor J. Linaburg; Javiera Araya; César A. Briceño (Case Reports in Ophthalmology, 2024)
Introduction: Maxillary ameloblastoma is a rare, slow-growing odontogenic tumor that can recur after surgical excision, be locally aggressive, and rarely develop systemic metastases. We describe the course and management of a patient with recurrent maxillary ameloblastoma with orbital invasion and systemic metastases, the fourth case of its kind to be described in the literature. Case Presentation: A 50-year-old female presented with left hyperglobus. A diagnosis of maxillary ameloblastoma was made based on biopsy and neuroimaging with MRI and CT. Surgical management included partial maxillectomy with orbital floor reconstruction, given the orbital invasion. Three years later, left hyperglobus recurred, and the patient was found to have orbital recurrence and lung metastases on PET imaging. The lung and orbital lesions have responded well to chemoradiation therapy without surgical intervention. Conclusion: Maxillary ameloblastoma is a rare tumor that typically arises from odontogenic tissues. Though considered benign, they can recur and in the case of our patient, metastasize. Complete surgical excision with wide surgical margins is associated with a shorter average time to recurrence and a lower incidence of metastasis. Cases of metastasis are managed with chemotherapy with or without adjuvant radiotherapy. Precision medicine may play a role in managing this entity in the future, given the discovery of differing profiles of maxillary ameloblastoma compared to mandibular. Ophthalmologists should be aware of this tumor as it can invade the orbit, resulting in significant ocular morbidity and mortality.